Linking Endogenous Factor Xa Activity, a Biologically Relevant Pharmacodynamic Marker, to Edoxaban Plasma Concentrations and Clinical Outcomes in the ENGAGE AF-TIMI 48 Trial. Issue 18 (30th October 2018) - Yin, Ophelia Q.P.; Antman, Elliott M.; Braunwald, Eugene; Mercuri, Michele F.; Miller, Raymond; Morrow, David; Ruff, Christian T.; Truitt, Kenneth; Weitz, Jeffrey I.; Giugliano, Robert P.
Abstract : Background: We previously reported exogenous antifactor Xa (FXa) activity as a pharmacokinetic surrogate marker for edoxaban plasma concentrations. Inhibition of endogenous FXa activity is a more biologically relevant pharmacodynamic measure of edoxaban activity. Here we describe the value of endogenous FXa activity as a pharmacodynamic marker linking edoxaban concentrations and clinical outcomes in the ENGAGE AF-TIMI 48 trial (Effective Anticoagulation With Factor Xa Next Generation in Atrial Fibrillation–Thrombolysis in Myocardial Infarction Study 48). Methods: In ENGAGE AF-TIMI 48, edoxaban was administered in higher dose (60/30 mg QD) and lower dose (30/15 mg QD) regimens. Both regimens incorporated a 50% dose reduction in patients with characteristics known to increase edoxaban concentration. Pharmacokinetic-pharmacodynamic modeling was performed in a subgroup of 3029 patients who had samples collected for endogenous FXa activity (measured using an assay after endogenous FX was activated with Russell viper venom). Results: Endogenous FXa activity decreased with increasing edoxaban concentrations of ⩽440 ng/mL, indicating that inhibition of endogenous FXa activity is saturated above this concentration threshold. Baseline endogenous FXa activity averaged 92.1±20.9% (relative to normal control samples) and was lower with older age, with lower body weight, and in male patients. Model-predicted 24-hour average percentages of inhibition of endogenous FXa activity were 35.8±5.18, 29.1±3.92, 21.9±3.80, and 16.4±2.70 for the higher dose edoxaban regimen 60 mg, dose-reduced higher dose edoxaban regimen 30 mg, lower dose edoxaban regimen 30 mg, and dose-reduced lower dose edoxaban regimen 15 mg groups, respectively. A greater average percentage of inhibition of endogenous FXa activity was associated with a lower incidence of ischemic stroke or systemic embolism and a higher risk of major bleeding ( P <0.001). In a typical subject, the predicted risks for the 10th and 90th percentiles of inhibition of endogenous FXa activity were 1.04% and 0.57% for incidence of ischemic stroke or systemic embolism and 1.35% and 2.33% for major bleeding, respectively. Conclusions: The extent of inhibition of endogenous FXa activity is influenced by edoxaban dosing and clinical characteristics, and it is associated with both antithrombotic benefit and risk of bleeding. This approach of linking endogenous FXa activity to clinical outcomes may be used to guide dose selection in future clinical trials, monitor patients in certain clinical scenarios, or refine the doses of oral FXa inhibitors in patients who require precise anticoagulation therapy. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00781391. Abstract : Supplemental Digital Content is available in the text.